ARTICLES - Dissanaike, Gishan; Markar, Imran (Journal of International Business Studies, 2009)
Some argue that corporate finance and governance practices were among the root causes of the Asian crisis. It is alleged that high and increasing corporate debt ratios were partly to blame. This claim is overstated: only South Korea and arguably Thailand had leverage ratios significantly above the G7 range, and only South Korea had an income-gearing ratio higher than the G7. Although the reliance on short-term debt was high, there was no drastic change in the maturity structure of debt before the crash. However, conventional factors are relatively more successful in explaining leverage for firms that were less closely connected to the relationship-based financing system. Our paper links to ongoing research on investor protection, cronyism, connections between business and government, and business groups. It ends by commenting on the 2008 financial crisis, currently engulfing the world, and highlights some similarities and paradoxes.